COVID-19, "Lockdown" and Achilles Tendon Ruptures - Murphy, B.; Miller, P.; Molloy, A.; O`Toole, G.; Curtin, P.; Flavin, R.; O`Shea, K.; Cassar-Gheiti, A.; Hurson, C. (Irish Medical Journal, 2021)
Introduction: The COVID-19 pandemic has affected the types of trauma being operated on by Orthopaedic surgeons. Lifting of restrictions around sports saw a sudden return to play for people after a period of inactivity. Achilles tendon ruptures are associated with these episodic athletes. We hypothesised that easing of "Lockdown" restrictions led to increased presentations of Achilles tendon ruptures vs. the same period in 2019. We conducted a case-control study to investigate. Methods: Data from electronic theatre logbooks of all operations performed from 27th March 2020 (Lockdown begins) to 31st July 2020 and 27th March 2019 to 31st July 2019 was collected. All operatively managed Achilles tendon ruptures were included. All other operations were excluded. Results: 772 total cases were performed in 2019. There were 17 Achilles tendon ruptures in that period (2.2%). 14 occurred after easing of restrictions. 580 total cases were performed in 2020. There were 13 Achilles tendon ruptures in that period (2.2%). 11 occurred after easing of restrictions and the return of sport. There was a greater incidence of Achilles tendon ruptures in 2019 vs. the equivalent "Lockdown" period in 2020. Conclusion: COVID-19 pandemic restrictions and return to play after inactivity does not increase the incidence or rate of Achilles tendon rupture.